2005
DOI: 10.1021/bi050527u
|View full text |Cite
|
Sign up to set email alerts
|

Role of the C-Terminus of the High-Conductance Calcium-Activated Potassium Channel in Channel Structure and Function

Abstract: The role of ion channels in cell physiology is regulated by processes occurring after protein biosynthesis, which are critical for both channel function and targeting of channels to appropriate cell compartments. Here we apply biochemical and electrophysiological methods to investigate the role of the high-conductance, calcium-activated potassium (Maxi-K) channel C-terminal domain in channel tetramerization, association with the beta1 subunit, trafficking of the channel complex to the cell surface, and channel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 37 publications
4
27
0
Order By: Relevance
“…In our hands, none of the constructs yielded functional BK channels, although each BK construct had the ER export sequence (Kwon and Guggino, 2004) attached to the truncated C terminus to enhance surface expression. Our data agree well with those from a report by Schmalhofer et al (2005), who also failed to detect channel activity in truncated BK 1-323 , BK 1-343 , BK 1-441 , and BK 1-651 constructs.…”
Section: U73122 Blocks Kir3 and Bk Channels 1209supporting
confidence: 93%
See 1 more Smart Citation
“…In our hands, none of the constructs yielded functional BK channels, although each BK construct had the ER export sequence (Kwon and Guggino, 2004) attached to the truncated C terminus to enhance surface expression. Our data agree well with those from a report by Schmalhofer et al (2005), who also failed to detect channel activity in truncated BK 1-323 , BK 1-343 , BK 1-441 , and BK 1-651 constructs.…”
Section: U73122 Blocks Kir3 and Bk Channels 1209supporting
confidence: 93%
“…Kir3.1 and, more so, BK channels show multiple and extensive regulatory domains between their last transmembrane domains (M2 and S6, respectively) and their C-terminal ends that can be accessed by various effectors to regulate channel gating (Meera et al, 1997;Lu et al, 2006;Salkoff et al, 2006;Logothetis et al, 2007). Because all our BK constructs failed to yield viable channels, consistent with Schmalhofer et al (2005), we designed mutant Kir3/Kir 2 channels to corroborate the hypothesis that the compounds target specific regions of the C terminus to inhibit Kir3 channel activity, as suggested by the sequence homologies between BK and Kir3 (Fig. 8).…”
Section: Discussionsupporting
confidence: 74%
“…However, this approach has been hampered by the inability to express functional cores in the absence of the tail. Previous analysis of truncated expression constructs of Slo1 channels found that their processing stalls in the endoplasmic reticulum (ER), they are not assembled into tetramers, they fail to be exported to the plasma membrane, or they are nonfunctional (24). We now show that core constructs without gating rings can be expressed by leaving a short region required for subunit tetramerization and by appending a small tail domain which facilitates processing and efficient export to the plasma membrane.…”
Section: +mentioning
confidence: 71%
“…5, G and H). The hSlo1 intracellular carboxyl-terminal end is known to play a role in Slo1 surface expression (33)(34)(35). The 1007 YNMLCFGIY 1015 sequence has several important features that may explain why its absence causes channel trapping inside the cell: (i) it has a di-hydrophobic motif (underlined), which may act as endoplasmic reticulum export signal (36), (ii) it has a targeting tyrosinebased motif YXX (bold; X, any amino acid and , hydrophobic residue), which is a general sorting sequence that directs proteins to various cellular compartments, including the plasma membrane (37), and (iii) it is located in a strategic position near another two sequences containing di-hydrophobic motifs, 996 YGKDFCKALK 1005 (in hSlo1, amino acids KD are replaced with DL, which add another dihydrophobic motif and a tyrosine-based motif) and 1047 DLIFCL 1052 , whose deletion is sufficient to prevent current development (38) and protein surface expression (35), respectively.…”
Section: Association Of Slo1 Protein With Caveolin-1 In Native Aorticmentioning
confidence: 99%